Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.jgo.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

High dose therapy and autologous hematopoietic stem cell transplantation in septuagenarians with non-Hodgkin lymphoma: Feasible, but for which patients?

Abstract: Editorial will accompany Hermet et al. “Autologous hematopoietic stem cell transplantation in elderly patients (≥ 70 years) with non-Hodgkin’s lymphoma: a French Society of Bone Marrow Transplantation and Cellular Therapy retrospective study.”

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Autologous stem cell transplantation has been recognized in the treatment of ischemic disease. Bone marrow mesenchymal stem cells (MSCs) are a rich source, easy to obtain, and have been safe in vitro amplification techniques, so are widely used in vascular tissue engineering [ 19 ]. Gładysz et al reported that MSCs play a therapeutic role in two ways after transplant to microvascular lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous stem cell transplantation has been recognized in the treatment of ischemic disease. Bone marrow mesenchymal stem cells (MSCs) are a rich source, easy to obtain, and have been safe in vitro amplification techniques, so are widely used in vascular tissue engineering [ 19 ]. Gładysz et al reported that MSCs play a therapeutic role in two ways after transplant to microvascular lesion.…”
Section: Discussionmentioning
confidence: 99%
“…NHL is the most common hematologic malignancy and the sixth cause of death from cancer in the USA [ 2 ]. High dose therapy (HDT) followed by autologous stem cell transplantation (ASCT) is a potentially curative therapeutic alternative for resistant or relapsed NHL patients [ 3 ]. Even for many cases of high risk NHL, the only potentially curative option is stem cell transplantation [ 4 ].…”
mentioning
confidence: 99%